Long-wavelength ( - Rochat, Michel; Hofstetter, Daniel; Beck, Mattias; Faist, Jérôme (My University, 2001)
Room-temperature operation of long-wavelength, Fabry-Perot and single-mode quantum-cascade lasers at lambda approximate to 16 mum is reported. Multimode emission with pulsed peak power up to 400 mW at -40 degreesC and 220 mW at 30 degreesC is demonstrated. Single-mode emission up to 60 mW peak power has been achieved at 30 degreesC. (C) 2001 American Institute of Physics.